Long-term magnesium orotate therapy in patients with mitral valve prolapse - A. I. Martynov; A. V. Akatova; O. P. Nikolin (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To assess the effectiveness of long-term treatment with magnesium orotate (Magnerot®), as a pathogenetic therapy, in patients with mitral valve prolapse (MVP). Material and methods. In total, 31 MVP patients, administered Magnerot® (1500 mg/d) in three-month courses, twice a year, were followed up for 15 years. All patients underwent a complex clinical and instrumental examination which included clinical assessment, M-mode and B-mode echocardiography with simultaneous electrocardiography (ECG), standard 12-lead ECG at rest, 24-hour ECG monitoring, 24-hour blood pressure monitoring (BPM), and heart rate variability (HRV) assessment. Results. The study identified the specifics of clinical features, their association with the degree of phenotypical manifestation of connective tissue dysplasia, ECG changes, heart valve structure, autonomic homeostasis, BP levels and circadian profile, and sympathetic and parasympathetic tone. There was a significant reduction in mean and maximal heart rate, the number of tachycardia episodes, QTc interval duration, as well as the incidence of paroxysmal supraventricular tachycardia, supraventricular and ventricular extrasystolia. Maximal systolic and diastolic BP (SBP, DBP) levels, BP load, and initially increased SBP and DBP variability were significantly reduced. The retrospective analysis results showed a normalisation of the above-mentioned parameters in all participants. The sympathetic tone decreased, as demonstrated by a twofold reduction in the number of patients with sympathicotonia, a threefold increase in the number of participants with vagotonia, and a five-fold increase in the number of individuals with balanced sympathetic and parasympathetic tone. Conclusion. One-half of the examined MVP patients, who were administered a long-term Magnerot® therapy, have demonstrated a significant improvement in the treatment effectiveness index.